Disease-specific monoclonal antibodies targeting glutamate decarboxylase impair GABAergic neurotransmission and affect motor learning and behavioral functions - Mario U Manto; Jerome eHonorat; Christiane Susanne Hampe; Rafael eGuerra-Narbona; Juan Carlos eLópez Ramos; José M Delgado-García; Fumihito eSaitow; Hidenori eSuzuki; Yuchio eYanagawa; Hidehiro eMizusawa; Hiroshi eMitoma (Frontiers in Behavioral Neuroscience, 2015)
Autoantibodies to the smaller isoform of glutamate decarboxylase can be found in patients with type 1 diabetes and a number of neurological disorders, including stiff-person syndrome, cerebellar ataxia and limbic encephalitis. The detection of disease-specific autoantibody epitopes led to the hypothesis that distinct glutamate decarboxylase autoantibodies may elicit specific neurological phenotypes. We explored the in vitro/in vivo effects of well-characterized monoclonal glutamate decarboxylase antibodies. We found that glutamate decarboxylase autoantibodies present in patients with stiff person syndrome (n = 7) and cerebellar ataxia (n = 15) recognized an epitope distinct from that recognized by glutamate decarboxylase autoantibodies present in patients with type 1 diabetes mellitus (n = 10) or limbic encephalitis (n = 4). We demonstrated that the administration of a monoclonal glutamate decarboxylase antibody representing this epitope specificity (1) disrupted in vitro the association of glutamate decarboxylase with γ-Aminobutyric acid containing synaptic vesicles, (2) depressed the inhibitory synaptic transmission in cerebellar slices with a gradual time course and a lasting suppressive effect, (3) significantly decreased conditioned eyelid responses evoked in mice, with no modification of learning curves in the classical eyeblink-conditioning task, (4) markedly impaired the facilitatory effect exerted by the premotor cortex over the motor cortex in a paired-pulse stimulation paradigm, and (5) induced decreased exploratory behavior and impaired locomotor function in rats. These findings support the specific targeting of glutamate decarboxylase by its autoantibodies in the pathogenesis of stiff-person syndrome and cerebellar ataxia. Therapies of these disorders based on selective removal of such glutamate decarboxylase antibodies could be envisioned.